The Effect of Teacher Certification and Work Discipline on the Performance of State Junior High School Teachers in Tebing Tinggi District - Apriani, Utami; Destiniar, Destiniar; Harapan, Edi (Gema Wiralodra, 2024)
This study aims to analyze the influence of teacher certification and work discipline on the performance of State Junior High School teachers in Tebing Tinggi District. The method used in this study is a quantitative method with a survey approach. Data was collected through a questionnaire distributed to teachers who teach at several State Junior High Schools in Tebing Tinggi District. From the statistical results, there is an influence of teacher certification and work discipline simultaneously on the performance of State Junior High School teachers in Tebing Tinggi District from the results of the analysis of values of F-clung = 13.587 > F-table = 0.967 and able to contribute a simultaneous influence of 33.4%. The results of the study show that certification and work discipline have a significant impact on teacher performance. Teachers with certification tend to perform better than teachers who are not certified. In addition, work discipline also plays a vital role in improving teacher performance. Teachers with high work discipline are more effective in carrying out their duties and achieving educational goals. This study concludes that certification and work discipline are essential in improving teacher performance. Therefore, efforts to improve teacher performance should include a broader certification program and an improvement in work discipline through various training and supportive policies